Extent and risks of antidepressant off-label use in children and adolescents in Germany between 2004 and 2011 - Schröder, Carsten; Dittmann, Ralf (Pharmacoepidemiology and drug safety, 2017)
Purpose So far, only little is known about antidepressant off-label use in pediatric patients. This is the first study examining the prevalence and the risks of off-label antidepressant prescriptions in minors over time in Germany and analyzing patterns regarding age, sex, drug class, and type of off-label use. Methods We used claims data of about two million individuals (<18 y) to calculate the share of off-label antidepressant prescriptions for the years 2004 to 2011, stratified by age, sex, and drug class. Off-label prescriptions were analyzed regarding underlying diagnoses, the prescribing doctor's specialty, and the type of off-label use. Incidence rates of adverse events were calculated for off- and on-label use, and the risk of suicidal events associated with off- or on-label use was examined in a nested case-control study. Results The prevalence of off-label prescriptions decreased from 58.0% to 40.9%. Selective serotonin reuptake inhibitors were more frequently prescribed off-label than tricyclic antidepressants (37.7% vs 17.5% in 2011). The most common type of off-label use was off-label use by age, followed by off-label use by indication, and off-label use by contraindication. Adverse events were rare with no significant differences between on- and off-label use. Conclusions Although off-label antidepressant use in minors decreased over time, it is still common. However, this rather indicates a lack of approved drugs for the treatment of depression in this population than inappropriate medical treatment. This is supported by the fact that off-label use was not associated with a higher risk of adverse events than on-label use.